Komponen Bioaktif Dalam Daging dan Sifat Fungsionalnya: Sebuah Kajian Pustaka - Khothibul Umam Al Awwaly; Suharjono Triatmojo; Yuny Erwanto; Wayan Tunas Artama (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2015)
Consumer awareness in meat and meat products is generally recognized as a good source of food, with high biological value protein, B group vitamins, minerals and minor elements like several other bioactive compounds that are beneficial to the human body. But in many cases, a processing error is affecting the bioactive compounds of functional foods and consumer impression are relatively negative to some levels of substances in meat such as fat, cholesterol, saturated fatty acids, salt and other substances, which however also involves a diseases of western society such as cardiovascular diseases, respiratory, carcinogenesis, obesity, impaired immune system and accelerate the aging process. Hence there is a need for adequate information related to favorable nutritional value of meat that has not been widely disclosed. Bioactive components in the meat can be anserin, karnosin and bioactive peptides. The generation of bioactive components in the meat in the form of bioactive peptides can be done in three ways: (1) aging or storage of meat, (2) meat fermentation, and (3) the enzyme treatment. Functional properties of bioactive components in meat varies greatly as an antioxidant, antihypertensive, antimicrobial, anticancer and immunomodulatory.